Serum-free growth of normal and tumor mouse mammary epithelial cells in primary culture. - Imagawa, W (1982)
Freshly isolated normal and tumor mouse mammary epithelial cells embedded within a collagen gel matrix undergo sustained growth when cultured for as long as 3 wk in a serum-free medium composed of a 1:1 (vol/vol) mixture of Hepesbuffered Ham's F12 and Dulbecco's modified Eagle's medium supplemented with insulin, epidermal growth factor (EGF), transferrin, bovine serum albumin fraction V, and cholera toxin. Of these additives, only insulin, EGF, and albumin are required for the growth of most normal cells. Albumin is not always an absolute requirement for growth but greatly enhances it. Lithium has been found to stimulate the growth of normal cells and can replace EGF. The collagen matrix culture system allows sustained growth of primary cultures of both normal and neoplastic mammary epithelium in serum-free conditions. This serum-free system will be useful in identifying and investigating the role of hormones, growth factors, and nutritional factors in regulating the growth of mammary epithelial cells.